2004
DOI: 10.2337/diabetes.53.suppl_3.s140
|View full text |Cite
|
Sign up to set email alerts
|

Desensitization of Insulin Secretion by Depolarizing Insulin Secretagogues

Abstract: Prolonged stimulation of insulin secretion by depolarization and Ca2؉ influx regularly leads to a reversible state of decreased secretory responsiveness to nutrient and nonnutrient stimuli. This state is termed "desensitization." The onset of desensitization may occur within 1 h of exposure to depolarizing stimuli. Desensitization by exposure to sulfonylureas, imidazolines, or quinine produces a marked cross-desensitization against other ATP-sensitive K ؉ channel (K ATP channel)-blocking secretagogues. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 88 publications
3
19
1
Order By: Relevance
“…These results are in accordance with previous studies reporting a negative impact of prolonged exposure to some sulfonylureas on islet cell function (Rustenbeck et al, 2004b;Del Guerra et al, 2005). In addition, the sulfonylureas glibenclamide and tolbutamide are known to elicit apoptosis in ␤-cells or pancreatic cell lines (Efanova et al, 1998;Iwakura et al, 2000;Rustenbeck et al, 2004a;Maedler et al, 2004Maedler et al, , 2005.…”
Section: Discussionsupporting
confidence: 82%
“…These results are in accordance with previous studies reporting a negative impact of prolonged exposure to some sulfonylureas on islet cell function (Rustenbeck et al, 2004b;Del Guerra et al, 2005). In addition, the sulfonylureas glibenclamide and tolbutamide are known to elicit apoptosis in ␤-cells or pancreatic cell lines (Efanova et al, 1998;Iwakura et al, 2000;Rustenbeck et al, 2004a;Maedler et al, 2004Maedler et al, , 2005.…”
Section: Discussionsupporting
confidence: 82%
“…Thus, the insulin secretion by K ϩ depolarization has not only quantitatively but also qualitatively different characteristics, depending on the K ϩ concentration. The virtual inability of 15 mM K ϩ to increase secretion in the presence of basal glucose confirms our recent observation (15) but is in apparent conflict with another report that 15 mM K ϩ was moderately effective in the presence of 5 mM glucose and elicited a desensitization of secretion, a typical feature of a depolarizing secretagogue (30,39). However, in the latter study rat islets were used, which are known to have a higher glucose sensitivity than mouse islets (21,40).…”
Section: Discussioncontrasting
confidence: 54%
“…The reason that TNF-a did not inhibit KCl-stimulated insulin secretion was not clear, but a lack of impairment of KClstimulated insulin secretion was frequently observed in b-cells that were not responsive to glucose. Several studies have reported that insulin secretion stimulated by membrane-depolarizing agents such as KCl and arginine was not blunted in secretagogueinduced desensitized b-cells or islet b-cells isolated from diabetic patients (Rustenbeck et al 2004, Del Guerra et al 2005 . A recent report that prevention of prenylation of small G-proteins, which may be involved in insulin granule movement, inhibited GSIS but not KCl-stimulated insulin secretion supports the idea that b-cells with functional impairment at the step of Ca 2C influx or insulin exocytosis can respond to KCl (Veluthakal et al 2007).…”
Section: Discussionmentioning
confidence: 99%